2011
DOI: 10.1182/blood-2010-07-298992
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of CD4+CD25+CD127lowFOXP3+ regulatory T cells in HIV-infected pregnant women

Abstract: Pregnancy represents a major challenge to immunologic tolerance. How the fetal "semiallograft" evades maternal immune attack is unknown. Pregnancy success may involve alteration of both central (thymic) and peripheral tolerance mechanisms. HIV infection is characterized by CD4 ؉ T-cell depletion, chronic immune activation, and altered lymphocyte subsets. We studied immunologic consequences of pregnancy in 20 HIV-infected women receiving highly active antiretroviral therapy (HAART), and for comparison in 16 HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
1
16
0
1
Order By: Relevance
“…This included CD4+CD25+FoxP3+, CD8+CD25+FoxP3+, CD4+TGFβ+ and CD4+IL10+ Treg and it was most likely an effect of HIV infection, which is in agreement with previous findings in non-pregnant HIV-infected adults [6], [8], [44], [45]. Our findings, however, contrast with a recently published study of pregnant women, which showed lower CD4+CD25+FoxP3+CD127 low Treg frequencies in HIV-infected compared with uninfected women during the 2nd trimester of pregnancy[46]. The duration of HAART of the HIV-infected subjects differed between the two studies, with most of our subjects starting HAART during pregnancy, while in the study by Kolte et al, most subjects were on HAART before pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…This included CD4+CD25+FoxP3+, CD8+CD25+FoxP3+, CD4+TGFβ+ and CD4+IL10+ Treg and it was most likely an effect of HIV infection, which is in agreement with previous findings in non-pregnant HIV-infected adults [6], [8], [44], [45]. Our findings, however, contrast with a recently published study of pregnant women, which showed lower CD4+CD25+FoxP3+CD127 low Treg frequencies in HIV-infected compared with uninfected women during the 2nd trimester of pregnancy[46]. The duration of HAART of the HIV-infected subjects differed between the two studies, with most of our subjects starting HAART during pregnancy, while in the study by Kolte et al, most subjects were on HAART before pregnancy.…”
Section: Discussionsupporting
confidence: 89%
“…The anti-inflammatory functions of Treg involve production of, for example, cytokines such as IL-10, which could at least partially explain the increased concentrations of IL-10 we observed in peripheral plasma in parallel with the different chemokines mentioned earlier (Boström S & Ibitokou S, unpublished data). The impact that any of the infection-mediated changes in circulating Treg observed here may have on the reported gestational age-related fluctuations in the frequency of Treg in PBMC during normal, healthy pregnancies remains to be determined [4], [47], [48]. Whether such fluctuations occur during ‘normal’ healthy pregnancies in African populations in any case requires confirmation.…”
Section: Discussionmentioning
confidence: 74%
“…Although systematically confirmed clinically, estimations on incidence rate of pregnancy presented in our study were initially based on women self-report of the last menstruation period. Bearing in mind that miscarriages and abortions are very frequent during the early months of pregnancy (27) and HIV infection has been pointed out as an important cause (28), we suspect that a substantial number of pregnancies may have gone undetected. The former and the significant proportion of dropouts contributed clearly to an underestimation of the pregnancy incidence reported.…”
Section: Discussionmentioning
confidence: 99%